Composite paper-based flexible sensing material and preparation method thereof and strain sensor

By dispersing MXene in cellulose paper and compounding with dynamic polymer prepolymers, a composite paper-based flexible sensing material is formed, which solves the problem of insufficient mechanical properties and moisture resistance of the sensor substrate material, and achieves flexible sensing materials with high mechanical properties and water resistance, which are suitable for a variety of application scenarios.

CN116770636BActive Publication Date: 2025-04-18SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310728190.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2025-04-18
Estimated Expiration
2043-06-19

AI Technical Summary

Technical Problem

The existing flexible sensor substrate materials have poor mechanical properties and strong hygroscopicity, making it difficult to meet the requirements of special electronic devices, and the weak affinity between the sensing material and the polymer substrate leads to interface peeling, limiting the durability of the sensor.

Method used

By dispersing the MXene evenly in water, immersing it in cellulose paper and drying, repeating several times until the resistance value is stable, and then immersing the cellulose paper in a dynamic polymer prepolymer for thermal curing to form a composite paper-based flexible sensing material. This material uses epoxy soybean oil and biomass dibasic acid to construct a hydroxy-ester dynamic polymer prepolymer through an epoxy ring-opening reaction, enhancing the mechanical properties and water resistance of the material.

Benefits of technology

The mechanical properties and water resistance of composite paper-based flexible sensing materials have been improved, the tensile fracture strength reaches 22MPa, the surface is hydrophobic, the water contact angle reaches 110.6°, the strain index GF = 8.5, the response time is 0.41s, and the stability is greater than 1,000 bending strain cycles. It is suitable for human motion detection and high humidity environment monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004299764940000011
    Figure HDA0004299764940000011
  • Figure HDA0004299764940000012
    Figure HDA0004299764940000012
  • Figure HDA0004299764940000013
    Figure HDA0004299764940000013
Patent Text Reader

Abstract

The present invention provides a composite paper-based flexible sensing material and a preparation method thereof and a strain sensor, comprising the following steps: step 1, uniformly dispersing MXene in water to obtain a conductive dispersion; step 2, immersing cellulose paper in the conductive dispersion, then taking it out and drying it, and measuring the resistance value of the cellulose paper; step 3, repeating step 2 until the resistance value of the cellulose paper reaches a stable state to obtain MXene paper; step 4, immersing the MXene paper obtained in step 3 in a dynamic polymer prepolymer, then taking it out and thermally curing it to obtain a composite paper-based flexible sensing material; the composite paper-based flexible sensing material has good mechanical properties and water resistance, and expands the application field of paper-based flexible sensor devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of flexible sensing technology, and in particular to a composite paper-based flexible sensing material with enhanced mechanical properties and water resistance, a preparation method thereof, and a strain sensor. Background Art

[0002] Flexible sensors have broad application prospects in the fields of artificial intelligence, wearable devices, electronic skin, health and sports monitoring. To achieve the flexibility of sensors, the key is flexible substrate materials. At present, common materials include films of polyimide (PI) or polyethylene terephthalate (PET) and elastomers of polyurethane (PU) or polydimethylsiloxane (PDMS). These materials have good flexibility and dimensional stability and still occupy an important position in flexible sensors. However, on the one hand, these substrate materials are difficult to degrade, which will lead to the enrichment of electronic waste. On the other hand, the weak affinity between the sensing material and the polymer substrate will cause the interface peeling of the sensing material during deformation, limiting the durability of the sensor. Therefore, finding high-performance green and environmentally friendly materials as the substrate of flexible sensors has received more and more attention.

[0003] Paper made from plant cellulose fibers is a flexible, low-cost, lightweight, environmentally friendly, biodegradable and renewable material that has been gradually applied to the development of green electronic devices in recent years. Compared with synthetic polymer substrate materials, paper can not only meet the requirements of insulation and good flexibility, but also the abundant hydroxyl groups on the surface of cellulose fibers and the porous structure formed by the randomly distributed fiber network are conducive to the interfacial bonding of sensing materials. However, cellulose paper has certain shortcomings as a substrate material, mainly manifested in: (1) poor mechanical properties, which make it difficult to meet the requirements of special electronic devices for material mechanical properties; (2) strong hygroscopicity, which is easily affected by high humidity environments. Strengthening and encapsulating paper-based materials is expected to solve the above problems. For example, Duan et al. used simple polyimide (PI) tape encapsulation to prevent paper-based sensors from being affected by humidity and water. The specific articles published are as follows: "Duan Z, Jiang Y, Huang Q, et al. Integrated cross-section interface engineering and surface encapsulating strategy: A high-response, waterproof, and low-cost paper-based bending strain sensor [J]. Journal of Materials Chemistry C, 2021, 9 (39): 14003-14011.". Guo et al. assembled the composite paper-based sensing material between degradable polylactic acid (PLA) sheets to solve the problem of strong hygroscopicity of the paper-based material, but the mechanical properties of the paper-based material were not significantly improved. The specific articles published are as follows: "Guo Y, Zhong M, Fang Z, et al. A Wearable Transient Pressure Sensor Made with MXene Nanosheets for Sensitive Broad-Range Human-Machine Interfacing [J]. Nano Letters, 2019, 19 (2): 1143-1150.". Therefore, it is urgent to develop new material systems to provide solutions to the above problems. Summary of the invention

[0004] In view of the problems existing in the above-mentioned prior art, the present invention provides a composite paper-based flexible sensing material and a preparation method thereof and a strain sensor. The composite paper-based flexible sensing material has good mechanical properties and water resistance, which expands the application field of paper-based flexible sensor devices.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a composite paper-based flexible sensing material comprises the following steps:

[0007] Step 1, uniformly dispersing MXene in water to obtain a conductive dispersion;

[0008] Step 2, immersing the cellulose paper in the conductive dispersion, then taking it out to dry, and measuring the resistance value of the cellulose paper;

[0009] Step 3, repeating step 2 until the resistance value of the cellulose paper reaches a stable value, thereby obtaining MXene paper;

[0010] Step 4, immersing the MXene paper obtained in step 3 into a dynamic polymer prepolymer, and then taking it out and thermally curing it to obtain a composite paper-based flexible sensing material;

[0011] The dynamic polymer prepolymer is obtained in advance by the following method: epoxy soybean oil and dibasic acid are subjected to epoxy ring-opening reaction in the presence of a catalyst to obtain the dynamic polymer prepolymer.

[0012] Preferably, in step 2, the drying is performed at 40 to 90° C. for 10 to 50 min.

[0013] Preferably, in step 3, the condition for judging whether the resistance value of the cellulose paper reaches stability is that the ratio of the difference between the last two resistance values ​​of the cellulose paper to the last resistance value of the cellulose paper is less than 5%.

[0014] Preferably, in step 4, the thermal curing is specifically: pre-curing at 90-120° C. for 4-6 hours, then curing at 110-140° C. for 10-12 hours, and finally post-curing at 130-160° C. for 2-4 hours.

[0015] Preferably, the catalyst is 1,8-diazabicyclo[5.4.0]undec-7-ene.

[0016] Preferably, the epoxy ring-opening reaction is specifically carried out at 90-120° C. for 10-20 min.

[0017] Preferably, the molar ratio of the catalyst to the carboxyl group in the dibasic acid is (0.01-0.10):1, and the molar ratio of the carboxyl group in the dibasic acid to the epoxy group in the epoxidized soybean oil is (0.3-1.3):1.

[0018] Preferably, the dibasic acid is one of itaconic acid, adipic acid and sebacic acid.

[0019] The composite paper-based flexible sensing material is obtained by the preparation method.

[0020] A strain sensor comprises the composite paper-based flexible sensing material.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention provides a method for preparing a composite paper-based flexible sensing material with enhanced mechanical properties and water resistance, using biomass-derived epoxy soybean oil and biomass dibasic acid as raw materials, using the ring-opening reaction of the epoxy group to construct a hydroxyl-ester dynamic polymer prepolymer, and then compounding it with a conductive MXene paper-based sensing material by an impregnation method, so that the dynamic polymer prepolymer infiltrates into the pores of the fiber three-dimensional network and wraps around the cellulose, and after thermal curing, a hydroxyl-ester cross-linked network is formed, so that the relatively loose paper sheet structure itself becomes tighter, and at the same time, it depends on the strengthening effect and water resistance of the dynamic polymer, so that the performance of the composite paper sheet is significantly improved, and the obtained composite paper-based flexible sensing material has good mechanical properties and water resistance. In addition, all raw materials used in the composite paper-based flexible sensing material of the present invention, including cellulose paper, epoxy soybean oil, and biomass dibasic acid, are all biomass-derived, degradable, easy to handle, and pollution-free.

[0023] The composite paper-based flexible sensing material of the present invention is further made into a sensor through simple assembly. The sensor has excellent mechanical properties, a tensile breaking strength of 22MPa, a hydrophobic surface, and a water contact angle of 110.6°. As a strain sensor, the strain index GF=8.5, the response time is 0.41s, and the stability is greater than 1000 bending strain cycles. It can be successfully applied to motion detection of joints such as fingers and wrists, and can also be used for force monitoring during packaging and transportation, including impact, rollover, etc. More importantly, the sensor has long-term stability and is not affected by high humidity environments. It has potential application value in the fields of human motion monitoring, high humidity environment monitoring, and intelligent packaging and transportation. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a flow chart for preparing the composite paper-based flexible sensor of the present invention.

[0025] Figure 2 This is a schematic diagram of the structure of the composite paper-based flexible sensor of the present invention.

[0026] Figure 3 This is a Fourier transform infrared spectrum of itaconic acid, epoxy soybean oil, cellulose paper, and composite paper-based flexible sensing material in Example 2 of the present invention.

[0027] Figure 4 This is a scanning electron microscope photograph of the cross section of the composite paper-based flexible sensing material in Example 2 of the present invention at 100 μm.

[0028] Figure 5This is a scanning electron microscope photograph of the plane of the composite paper-based flexible sensing material in Example 2 of the present invention at 100 μm.

[0029] Figure 6 It is the stress and strain of the cellulose paper, MXene paper, and composite paper-based flexible sensing materials in Example 2 of the present invention.

[0030] Figure 7 It is the water contact angle of cellulose paper, MXene paper, and composite paper-based flexible sensing material in Example 2 of the present invention.

[0031] Figure 8 This is a strain index diagram of the composite paper-based flexible sensor in Example 2 of the present invention.

[0032] Fig. 9 This is a sensing effect diagram of the composite paper-based flexible sensor in Example 2 of the present invention.

[0033] Fig.10 is the response time of the composite paper-based flexible sensor in Example 2 of the present invention.

[0034] Fig.11 This is 1000 cycles of the composite paper-based flexible sensor in Example 2 of the present invention.

[0035] Fig.12 Response curves of the composite paper-based flexible sensor in Example 2 of the present invention in different humidity environments.

[0036] Fig.13 The composite paper-based flexible sensor in Example 2 of the present invention simulates the transportation process of the packaging box and monitors the output signal when the packaging box is hit or overturned.

[0037] In the figure: cellulose paper strip 1, conductive dispersion 2, MXene paper 3, MXene paper-based sensor 4, dynamic polymer prepolymer 5, composite paper-based flexible sensor 6, composite paper-based flexible sensing material 7, conductive copper glue 8, wire 9. DETAILED DESCRIPTION

[0038] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.

[0039] The preparation method of the composite paper-based flexible sensing material of the present invention is as follows: Figure 1 As shown, the following steps are included:

[0040] Step 1, uniformly disperse MXene in deionized water, the mass ratio of MXene to deionized water is (0.1-2): (70-100), and ice bath ultrasonic treatment is performed for 2 hours to obtain a uniform conductive dispersion 2.

[0041] Step 2: Cut the cellulose paper into cellulose paper strips 1 with a length of 3 cm and a width of 1 cm, immerse the strips in the conductive dispersion for 3 to 5 seconds, and then dry them at 40 to 90° C. for 10 to 50 minutes to obtain a cellulose paper strip coated with a single layer of MXene, and measure the resistance.

[0042] Step 3, repeat step 2 until the resistance value reaches stability. When the coating is applied more times, the resistance change of the sensing material is less than 5%, that is, when the ratio of the difference between the resistance values ​​of the last two cellulose paper strips and the resistance of the last cellulose paper is less than 5%, the resistance reaches stability, and the number of coatings at this time is defined as the optimal number of coatings. After 4 to 12 coatings, MXene paper 3 is obtained. The MXene nanosheets form a conductive path on the surface of the cellulose paper, which can realize the resistance change during the strain sensing process. Connect the MXene paper 3 to the wire 9 with a conductive copper glue 8 to obtain a MXene paper-based sensor 4.

[0043] Step 4, using 1,8-diazabicyclo[5.4.0]undec-7-ene as a catalyst, heating and stirring the epoxy soybean oil and the dibasic acid at 90-120° C. for 10-20 min to obtain a dynamic polymer prepolymer 5; the molar ratio of the catalyst to the carboxyl group in the dibasic acid is (0.01-0.10):1, the dibasic acid is one of itaconic acid, adipic acid, and sebacic acid, and the molar ratio of the carboxyl group in the dibasic acid to the epoxy group in the epoxy soybean oil is (0.3-1.3):1.

[0044] Step 5, immersing the MXene paper 3 in the MXene paper-based sensor 4 in a dynamic polymer prepolymer for 3 to 5 seconds, then pre-curing it at 90 to 120°C for 4 to 6 hours, then curing it at 110 to 140°C for 10 to 12 hours, and finally post-curing it at 130 to 160°C for 2 to 4 hours to obtain a composite paper-based flexible sensing material 7 with enhanced mechanical properties and water resistance and a composite paper-based flexible sensor 6 formed therefrom.

[0045] like Figure 2 As shown, the composite paper-based flexible sensing material 7 is connected to the wire 9 by using conductive copper glue 8 to assemble into a strain sensor.

[0046] Example 1

[0047] The method for preparing the composite paper-based flexible sensing material with enhanced mechanical properties and water resistance of the present invention comprises the following steps:

[0048] Step 1: Disperse MXene uniformly in deionized water with a mass ratio of MXene to deionized water of 0.1% and perform ice bath ultrasonic treatment for 2 h to obtain a uniform conductive dispersion.

[0049] Step 2: Cut the cellulose paper into cellulose paper strips with a length of 3 cm and a width of 1 cm, and completely immerse the paper strips in the conductive dispersion. After the paper strips are immersed for 5 seconds, they are hung in an oven and dried at 40°C for 50 minutes to obtain a MXene single-layer coated paper strip. Repeat the immersion and drying operations 7 times to obtain MXene paper.

[0050] Step 3, using 1,8-diazabicyclo[5.4.0]undec-7-ene as a catalyst, the molar ratio of the catalyst to the carboxyl group in itaconic acid is 1%, heating and stirring the epoxy soybean oil and itaconic acid at 120° C. for 20 minutes, the molar ratio of the carboxyl group in itaconic acid to the epoxy group in the epoxy soybean oil is 0.8, and a dynamic polymer prepolymer is obtained.

[0051] Step 4, completely immerse the MXene paper obtained in step 3 into the dynamic polymer prepolymer. After immersion for 5 seconds, hang it in an oven for pre-curing at 120°C for 6 hours, then cure it at 140°C for 12 hours, and finally post-cure it at 160°C for 4 hours to obtain a composite paper-based flexible sensing material with enhanced mechanical properties and water resistance.

[0052] Step 5, connecting the composite paper-based flexible sensing material obtained in step 4 with a conductive copper glue and a wire to assemble a strain sensor, with a strain index GF of 7.8 and a strain response time of 0.52 s.

[0053] Example 2

[0054] The method for preparing the composite paper-based flexible sensing material with enhanced mechanical properties and water resistance of the present invention comprises the following steps:

[0055] Step 1: Disperse MXene uniformly in deionized water with a mass ratio of MXene to deionized water of 0.2% and perform ice bath ultrasonic treatment for 2 h to obtain a uniform conductive dispersion.

[0056] Step 2: Cut the cellulose paper into cellulose paper strips with a length of 3 cm and a width of 1 cm, and completely immerse the paper strips in the conductive dispersion. After the paper strips are immersed for 5 seconds, they are hung in an oven and dried at 60°C for 15 minutes to obtain a MXene single-layer coated paper strip. Repeat the immersion and drying operations 6 times to obtain MXene paper.

[0057] Step 3, using 1,8-diazabicyclo[5.4.0]undec-7-ene as a catalyst, the molar ratio of the catalyst to the carboxyl group in itaconic acid is 5%, heating and stirring the epoxy soybean oil and itaconic acid at 120° C. for 15 minutes, the molar ratio of the carboxyl group in itaconic acid to the epoxy group in the epoxy soybean oil is 1.0, and a dynamic polymer prepolymer is obtained.

[0058] Step 4, completely immerse the MXene paper obtained in step 3 into the dynamic polymer prepolymer. After immersion for 5 seconds, hang it in an oven for pre-curing at 120°C for 6 hours, then cure it at 140°C for 12 hours, and finally post-cure it at 160°C for 4 hours to obtain a composite paper-based flexible sensing material with enhanced mechanical properties and water resistance.

[0059] Step 5, connecting the composite paper-based flexible sensing material obtained in step 4 with a conductive copper glue and a wire to assemble a strain sensor, with a strain index GF of 8.5 and a strain response time of 0.41 s.

[0060] Figure 3 This is the Fourier transform infrared spectra of itaconic acid, epoxy soybean oil, cellulose paper, and composite paper-based flexible sensing material (composite conductive paper). Itaconic acid is at 1703 cm -1 A characteristic peak appears at 3110 cm -1 He He 920cm -1 The broad peak at 830 cm is the stretching vibration peak and out-of-plane bending vibration peak of carboxyl hydroxyl O―H. -1 and 1747cm -1 The characteristic peaks appear at 3330cm, which are the bending vibration peak of the epoxy functional group and the stretching vibration peak of the ester carbonyl C=O. -1 A broad peak appears near 1735cm, which is the stretching vibration peak of a large number of hydroxyl groups -OH contained in cellulose molecules. -1 A characteristic peak appears at 1747 cm / s, which is the stretching vibration peak of the carbonyl C=O in the ester bond. Its stretching vibration frequency is lower than that of the ester carbonyl C=O (1747 cm / s) of epoxidized soybean oil. -1 ), this is because the ester group of the dynamic polymer is formed by the reaction of the carboxyl group in itaconic acid and the epoxy group in the epoxidized soybean oil, so there is a C=C next to the ester carbonyl C=O to conjugate with it, resulting in a decrease in the absorption frequency. In addition, the epoxy functional group belonging to the epoxidized soybean oil disappears. This shows that the dynamic polymer prepolymer forms a cross-linked dynamic polymer after curing in the cellulose paper.

[0061] Figure 4 and Figure 5 It reflects the microscopic morphology of the composite paper-based flexible sensing material. It can be seen that the dynamic polymer prepolymer penetrates into the pores of the fiber network and wraps the cellulose. After thermal curing, the loose paper sheet structure becomes more compact.

[0062] Figure 6 The stress and strain of cellulose paper, MXene paper, and composite paper-based flexible sensing materials. The composite paper-based flexible sensing material has the best mechanical properties, and its fracture strength (22.40MPa) is much higher than that of cellulose paper (13.10MPa) and MXene paper (13.94MPa).

[0063] Figure 7 The water contact angles of cellulose paper, MXene paper, and composite paper-based flexible sensing materials. The water contact angle of the composite paper-based flexible sensing material is 110.6°, which is larger than that of cellulose paper (0°) and MXene paper (98.2°), because the dynamic polymer is hydrophobic.

[0064] Figure 8 The curve of resistance change rate versus strain has a slope of strain index GF=8.5, which is higher than that of commercial constantan strain sensor (GF=2.0).

[0065] Fig. 9 The real-time curve of the resistance change rate over time measured during multiple reciprocating bending deformations (ε=0.7%) of the sensor is shown in Figure 1. The peak value of the measured curve is basically stable at 6%, indicating that the sensor has good working stability.

[0066] Fig.10 for Fig. 9 The local enlarged image shows that the response time of the sensor is 0.41s, which is similar to the parameters of the commercial constantan strain sensor (response time 0.3s).

[0067] Fig.11 After 1000 bending cycle tests on the sensor, the resistance change rate remained almost unchanged and remained at 4%, indicating that the sensor has good cycle stability.

[0068] Fig.12 The bending deformation response curve of the sensor when the ambient humidity is 50% and the bending deformation response curve after being placed in a constant temperature and humidity incubator at 25°C and 90% humidity for 24 hours. The resistance change rate and response time of the sensor are almost unchanged, indicating that the sensor is almost unaffected by the high humidity environment.

[0069] Fig.13 To simulate the transportation process of the packaging box, the output signal of the packaging box is monitored when it is hit or overturned. When the packaging box is hit or overturned, the sensor is subjected to different forces, deformed, and thus produces different output signals. When it encounters water spray, the output signal remains stable and the sensor works normally.

[0070] It can be seen that the sensor of this embodiment has excellent mechanical properties, a tensile fracture strength of 22MPa, a hydrophobic surface, and a water contact angle of 110.6°. As a strain sensor, the strain index GF=8.5, the response time is 0.41s, and the stability is greater than 1000 bending strain cycles. It can be successfully applied to motion detection of joints such as fingers and wrists. The sensing performance is not affected when placed in a high humidity environment for 24 hours.

[0071] Example 3

[0072] The method for preparing the composite paper-based flexible sensing material with enhanced mechanical properties and water resistance of the present invention comprises the following steps:

[0073] Step 1: Disperse MXene uniformly in deionized water with a mass ratio of MXene to deionized water of 0.3% and perform ice bath ultrasonic treatment for 2 h to obtain a uniform conductive dispersion.

[0074] Step 2: Cut the cellulose paper into cellulose paper strips with a length of 3 cm and a width of 1 cm, and completely immerse the paper strips in the conductive dispersion. After the paper strips are immersed for 5 seconds, they are hung in an oven and dried at 90°C for 10 minutes to obtain a MXene single-layer coated paper strip. Repeat the immersion and drying operations 5 times to obtain MXene paper.

[0075] Step 3, using 1,8-diazabicyclo[5.4.0]undec-7-ene as a catalyst, the molar ratio of the catalyst to the carboxyl group in itaconic acid is 10%, heating and stirring the epoxy soybean oil and itaconic acid at 120° C. for 10 minutes, the molar ratio of the carboxyl group in itaconic acid to the epoxy group in the epoxy soybean oil is 1.2, and a dynamic polymer prepolymer is obtained.

[0076] Step 4, completely immerse the MXene paper obtained in step 3 into the dynamic polymer prepolymer. After immersion for 5 seconds, hang it in an oven for pre-curing at 120°C for 4 hours, then cure it at 140°C for 10 hours, and finally post-cure it at 160°C for 2 hours to obtain a composite paper-based flexible sensing material with enhanced mechanical properties and water resistance.

[0077] Step 5, connecting the composite paper-based flexible sensing material obtained in step 4 with a conductive copper glue and a wire to assemble a strain sensor, with a strain index GF of 6.9 and a strain response time of 0.48 s.

[0078] Example 4

[0079] The method for preparing the composite paper-based flexible sensing material with enhanced mechanical properties and water resistance of the present invention comprises the following steps:

[0080] Step 1: Disperse MXene uniformly in deionized water with a mass ratio of MXene to deionized water of 0.1% and perform ice bath ultrasonic treatment for 2 h to obtain a uniform conductive dispersion.

[0081] Step 2: Cut the cellulose paper into cellulose paper strips with a length of 3 cm and a width of 1 cm, and completely immerse the paper strips in the conductive dispersion. After the paper strips are immersed for 5 seconds, they are hung in an oven and dried at 40°C for 50 minutes to obtain a MXene single-layer coated paper strip. Repeat the immersion and drying operations 7 times to obtain MXene paper.

[0082] Step 3, using 1,8-diazabicyclo[5.4.0]undec-7-ene as a catalyst, the molar ratio of the catalyst to the carboxyl group in adipic acid is 1%, heating and stirring the epoxy soybean oil and adipic acid at 100° C. for 20 minutes, the molar ratio of the carboxyl group in adipic acid to the epoxy group in the epoxy soybean oil is 0.3, and obtaining a dynamic polymer prepolymer.

[0083] Step 4, completely immerse the MXene paper obtained in step 3 into the dynamic polymer prepolymer. After immersion for 5 seconds, hang it in an oven for pre-curing at 100°C for 6 hours, then cure it at 130°C for 12 hours, and finally post-cure it at 150°C for 4 hours to obtain a composite paper-based flexible sensing material with enhanced mechanical properties and water resistance.

[0084] Step 5, connecting the composite paper-based flexible sensing material obtained in step 4 with a conductive copper glue and a wire to assemble a strain sensor, with a strain index GF of 8.3 and a strain response time of 0.36 s.

[0085] Example 5

[0086] The method for preparing the composite paper-based flexible sensing material with enhanced mechanical properties and water resistance of the present invention comprises the following steps:

[0087] Step 1: Disperse MXene uniformly in deionized water with a mass ratio of MXene to deionized water of 0.2% and perform ice bath ultrasonic treatment for 2 h to obtain a uniform conductive dispersion.

[0088] Step 2: Cut the cellulose paper into cellulose paper strips with a length of 3 cm and a width of 1 cm, and completely immerse the paper strips in the conductive dispersion. After the paper strips are immersed for 5 seconds, they are hung in an oven and dried at 60°C for 15 minutes to obtain a MXene single-layer coated paper strip. Repeat the immersion and drying operations 6 times to obtain MXene paper.

[0089] Step 3, using 1,8-diazabicyclo[5.4.0]undec-7-ene as a catalyst, the molar ratio of the catalyst to the carboxyl group in adipic acid is 5%, heating and stirring the epoxy soybean oil and adipic acid at 100° C. for 15 minutes, the molar ratio of the carboxyl group in adipic acid to the epoxy group in the epoxy soybean oil is 0.8, and obtaining a dynamic polymer prepolymer.

[0090] Step 4, completely immerse the MXene paper obtained in step 3 into the dynamic polymer prepolymer. After immersion for 5 seconds, hang it in an oven for pre-curing at 100°C for 5 hours, then cure it at 130°C for 11 hours, and finally post-cure it at 150°C for 3 hours to obtain a composite paper-based flexible sensing material with enhanced mechanical properties and water resistance.

[0091] Step 5, connecting the composite paper-based flexible sensing material obtained in step 4 with a conductive copper glue and a wire to assemble a strain sensor, with a strain index GF of 7.4 and a strain response time of 0.44 s.

[0092] Example 6

[0093] The method for preparing the composite paper-based flexible sensing material with enhanced mechanical properties and water resistance of the present invention comprises the following steps:

[0094] Step 1: Disperse MXene uniformly in deionized water with a mass ratio of MXene to deionized water of 0.3% and perform ice bath ultrasonic treatment for 2 h to obtain a uniform conductive dispersion.

[0095] Step 2: Cut the cellulose paper into cellulose paper strips with a length of 3 cm and a width of 1 cm, and completely immerse the paper strips in the conductive dispersion. After the paper strips are immersed for 5 seconds, they are hung in an oven and dried at 90°C for 10 minutes to obtain a MXene single-layer coated paper strip. Repeat the immersion and drying operations 5 times to obtain MXene paper.

[0096] Step 3, using 1,8-diazabicyclo[5.4.0]undec-7-ene as a catalyst, the molar ratio of the catalyst to the carboxyl group in adipic acid is 10%, heating and stirring the epoxy soybean oil and adipic acid at 100° C. for 10 minutes, the molar ratio of the carboxyl group in adipic acid to the epoxy group in the epoxy soybean oil is 1.3, and obtaining a dynamic polymer prepolymer.

[0097] Step 4, completely immerse the MXene paper obtained in step 3 into the dynamic polymer prepolymer. After immersion for 5 seconds, hang it in an oven for pre-curing at 100°C for 4 hours, then cure it at 130°C for 10 hours, and finally post-cure it at 150°C for 2 hours to obtain a composite paper-based flexible sensing material with enhanced mechanical properties and water resistance.

[0098] Step 5, connecting the composite paper-based flexible sensing material obtained in step 4 with a conductive copper glue and a wire to assemble a strain sensor, with a strain index GF of 6.8 and a strain response time of 0.55 s.

[0099] Example 7

[0100] The method for preparing the composite paper-based flexible sensing material with enhanced mechanical properties and water resistance of the present invention comprises the following steps:

[0101] Step 1: Disperse MXene uniformly in deionized water with a mass ratio of MXene to deionized water of 0.1% and perform ice bath ultrasonic treatment for 2 h to obtain a uniform conductive dispersion.

[0102] Step 2: Cut the cellulose paper into cellulose paper strips with a length of 3 cm and a width of 1 cm, and completely immerse the paper strips in the conductive dispersion. After the paper strips are immersed for 5 seconds, they are hung in an oven and dried at 40°C for 50 minutes to obtain a MXene single-layer coated paper strip. Repeat the immersion and drying operations 7 times to obtain MXene paper.

[0103] Step 3, using 1,8-diazabicyclo[5.4.0]undec-7-ene as a catalyst, the molar ratio of the catalyst to the carboxyl group in sebacic acid is 1%, heating and stirring the epoxy soybean oil and sebacic acid at 90° C. for 20 minutes, the molar ratio of the carboxyl group in sebacic acid to the epoxy group in the epoxy soybean oil is 0.5, and obtaining a dynamic polymer prepolymer.

[0104] Step 4, completely immerse the MXene paper obtained in step 3 into the dynamic polymer prepolymer. After immersion for 5 seconds, hang it in an oven for pre-curing at 90°C for 6 hours, then cure it at 110°C for 12 hours, and finally post-cure it at 130°C for 4 hours to obtain a composite paper-based flexible sensing material with enhanced mechanical properties and water resistance.

[0105] Step 5, connecting the composite paper-based flexible sensing material obtained in step 4 with a conductive copper glue and a wire to assemble a strain sensor, with a strain index GF of 6.7 and a strain response time of 0.45 s.

[0106] Example 8

[0107] The method for preparing the composite paper-based flexible sensing material with enhanced mechanical properties and water resistance of the present invention comprises the following steps:

[0108] Step 1: Disperse MXene uniformly in deionized water with a mass ratio of MXene to deionized water of 0.2% and perform ice bath ultrasonic treatment for 2 h to obtain a uniform conductive dispersion.

[0109] Step 2: Cut the cellulose paper into cellulose paper strips with a length of 3 cm and a width of 1 cm, and completely immerse the paper strips in the conductive dispersion. After the paper strips are immersed for 5 seconds, they are hung in an oven and dried at 60°C for 15 minutes to obtain a MXene single-layer coated paper strip. Repeat the immersion and drying operations 6 times to obtain MXene paper.

[0110] Step 3, using 1,8-diazabicyclo[5.4.0]undec-7-ene as a catalyst, the molar ratio of the catalyst to the carboxyl group in sebacic acid is 5%, heating and stirring the epoxy soybean oil and sebacic acid at 90° C. for 15 minutes, the molar ratio of the carboxyl group in sebacic acid to the epoxy group in the epoxy soybean oil is 0.8, and obtaining a dynamic polymer prepolymer.

[0111] Step 4, completely immerse the MXene paper obtained in step 3 into the dynamic polymer prepolymer. After immersion for 5 seconds, hang it in an oven for pre-curing at 90°C for 5 hours, then cure it at 110°C for 9 hours, and finally post-cure it at 130°C for 3 hours to obtain a composite paper-based flexible sensing material with enhanced mechanical properties and water resistance.

[0112] Step 5, connecting the composite paper-based flexible sensing material obtained in step 4 with a conductive copper glue and a wire to assemble a strain sensor, with a strain index GF of 8.2 and a strain response time of 0.39 s.

[0113] Example 9

[0114] The method for preparing the composite paper-based flexible sensing material with enhanced mechanical properties and water resistance of the present invention comprises the following steps:

[0115] Step 1: Disperse MXene uniformly in deionized water with a mass ratio of MXene to deionized water of 0.3% and perform ice bath ultrasonic treatment for 2 h to obtain a uniform conductive dispersion.

[0116] Step 2: Cut the cellulose paper into cellulose paper strips with a length of 3 cm and a width of 1 cm, and completely immerse the paper strips in the conductive dispersion. After the paper strips are immersed for 5 seconds, they are hung in an oven and dried at 90°C for 10 minutes to obtain a MXene single-layer coated paper strip. Repeat the immersion and drying operations 5 times to obtain MXene paper.

[0117] Step 3, using 1,8-diazabicyclo[5.4.0]undec-7-ene as a catalyst, the molar ratio of the catalyst to the carboxyl group in sebacic acid is 10%, heating and stirring the epoxy soybean oil and sebacic acid at 90° C. for 10 minutes, the molar ratio of the carboxyl group in sebacic acid to the epoxy group in the epoxy soybean oil is 1.1, and obtaining a dynamic polymer prepolymer.

[0118] Step 4, completely immerse the MXene paper obtained in step 3 into the dynamic polymer prepolymer. After immersion for 5 seconds, hang it in an oven for pre-curing at 90°C for 4 hours, then cure it at 120°C for 10 hours, and finally post-cure it at 140°C for 2 hours to obtain a composite paper-based flexible sensing material with enhanced mechanical properties and water resistance.

[0119] Step 5, connecting the composite paper-based flexible sensing material obtained in step 4 with a conductive copper glue and a wire to assemble a strain sensor, with a strain index GF of 6.5 and a strain response time of 0.58 s.

Claims

1. A method for preparing a composite paper-based flexible sensing material, characterized in that: The following steps are involved: Step 1, uniformly dispersing MXene in water to obtain a conductive dispersion; Step 2, immersing the cellulose paper in the conductive dispersion, then taking it out to dry, and measuring the resistance value of the cellulose paper; Step 3, repeating step 2 until the resistance value of the cellulose paper reaches stability, thereby obtaining MXene paper; the judgment condition that the resistance value of the cellulose paper reaches stability is that the ratio of the difference between the last two resistance values ​​of the cellulose paper and the last resistance value of the cellulose paper is less than 5%; Step 4, immersing the MXene paper obtained in step 3 into a dynamic polymer prepolymer, and then taking it out and thermally curing it to obtain a composite paper-based flexible sensing material; The dynamic polymer prepolymer is obtained in advance by the following method: epoxy soybean oil and dibasic acid are subjected to epoxy ring-opening reaction in the presence of a catalyst to obtain the dynamic polymer prepolymer.

2. The method for preparing the composite paper-based flexible sensing material according to claim 1, characterized in that: In step 2, the drying is performed at 40-90° C. for 10-50 min.

3. The method for preparing the composite paper-based flexible sensing material according to claim 1, characterized in that: In step 4, the thermal curing is specifically: pre-curing at 90-120° C. for 4-6 hours, then curing at 110-140° C. for 10-12 hours, and finally post-curing at 130-160° C. for 2-4 hours.

4. The method for preparing the composite paper-based flexible sensing material according to claim 1, characterized in that: The catalyst is 1,8-diazabicyclo[5.4.0]undec-7-ene.

5. The method for preparing the composite paper-based flexible sensing material according to claim 1, characterized in that: The epoxy ring-opening reaction is specifically carried out by reacting at 90-120° C. for 10-20 minutes.

6. The method for preparing the composite paper-based flexible sensing material according to claim 1, characterized in that: The molar ratio of the catalyst to the carboxyl group in the dibasic acid is (0.01-0.10):1, and the molar ratio of the carboxyl group in the dibasic acid to the epoxy group in the epoxidized soybean oil is (0.3-1.3):

1.

7. The method for preparing the composite paper-based flexible sensing material according to claim 1, characterized in that: The dibasic acid is one of itaconic acid, adipic acid and sebacic acid.

8. A composite paper-based flexible sensing material obtained by the preparation method according to any one of claims 1 to 7.

9. A strain sensor, characterized in that: Comprising the composite paper-based flexible sensing material as described in claim 8.

Citation Information

Patent Citations

  • Flexible material with electric heating, humidity and VOC sensing characteristics and preparation method thereof

    CN113433173A

  • Super-hydrophobic paper-based difunctional flexible sensing material as well as preparation method and application thereof

    CN113463438A